Socio-political influence and youth’s leadership participation in Malaysia: A conceptual model extending TPB - Ekpe, Isidore; Mohamad, Mohd Rosli; Mat, Norsiah; Bah Simpong, Derweanna (2016)
The study seeks to investigate the possible reasons why most Malaysian youths have low participation in leadership activities in their communities.Could it be socio-cultural influence or political-legal factors? In doing this, the study aims to extend the Theory of Planned Behavior (TPB) to accommodate these factors noticed in Malaysian context.To seek answers to the above question, this study intends to adopt a survey (questionnaire) and a proportionate stratified random sampling method to collect data from youths in universities, polytechnics, secondary (cluster/special) schools in Malaysia peninsula.Data would be analyzed using descriptive statistics, multiple and hierarchical regression methods.Conclusion and recommendation are to be drawn from the findings for use by policy-makers and the various stakeholders in youth development in order to engender greater leadership participation among Malaysian youths.